IMPLEMENTATION OF TWO POINT BLOCK VARIABLE STEPS VARIABLE ORDER CODES FOR SOLVING ORDINARY DIFFERENTIAL EQUATIONS - Zanariah Abdul Majid (Proceedings of ICMSA, 2006)
The efficient codes are developed for solving Initial Value Problems (IVPs) of first order Ordinary Differential Equations (ODEs) using variable step size and order. The codes will contain the 2-point one block fully implicit block method of order 5, the 2-point two block fully implicit block method of order 7 and the 2-point three block fully implicit block method of order 9. These methods will estimate the numerical solution at two equally spaced points simultaneously within a block. The performances of the codes will be compared in terms of maximum error, total number of steps and execution times with the code 2PVSO in Omar [7].